SIGNIFICANCE OF CROSS COMBINATIONS FOR DEVELOPING Bt COTTON VARIETIES FOR OPTIMUM GENE (CRY1 AC) EXPRESSION LEVEL REQUIRED FOR BETTER BOLLWORM CONTROL - R. Anjum; M. J. Baloch; G. M. Baloch; Q. Chachar (Journal of Animal and Plant Sciences, 2019)
Level of Bt gene expression plays a vital role for better management of cotton bollworm. So the selection of cotton varieties having maximum gene expression at the period of bollworm attack ultimately manage pest better and yield more than the varieties failed to control bollworm attack. Thirty six cross combinations developed from six non-Bt females and six males containing Bt gene (Cry1Ac) were crossed in 6 × 6 North Carolina Design II fashion, were planted during the study period. All the crosses were evaluated to detect the Bt gene by immunostrip assay that exposed the presence of gene Cry1Ac in all crosses.  Through quantitative ELISA, Bt gene expression was quantified. Gene expression of Cry1Ac at 30 days after planting in all thirty six cross combinations varied from 1.003 to 2.814µg/g.  The top ten cross combinations having maximum gene expression (2.814 to 1.170 µg/g) were selected for further bioassay studies, the mortality% of Earias  spp in leaves at 60, 90 and 120 days after planting were also recorded.  At 60 days after planting (DAP) mortality was recorded 80% while at 120 DAP mortality percentage dropped to unacceptable level and ranged between 33 to 28%. However some combinations proved effective at 120 DAP as well. Our studies proved that selection of combinations can improve pest management and ultimately enhance yield for the betterment of the farmers and for the country as a whole.
Keywords: Bt Cotton; gene ( Cry1Ac) expression; Cross combinations; bollworm